Influence of different directions of the Kinesio tape application on the rectus femoris muscle on the quality of the knee flexion pattern in a prone position - Toboła, Katarzyna; Jankowicz-Szymańska, Agnieszka (Health Promotion & Physical Activity, 2024)
Introduction: Movement patterns are sequences of movements performed automatically. Due to sedentary lifestyles, lack of physical activity, and poor posture habits, these patterns are often inappropriate. Analysis and re-education of the performance of movement patterns are the methods of preventing pain and musculoskeletal dysfunction. The research aimed to compare the effectiveness of different directions of the Kinesio tape application on knee flexion range of motion in young women. Material and methods: The study involved 40 women aged 21–25; 10 women with a normal range of active knee flexion measured in the prone position and 30 women with limited active flexion of both knee joints, who were randomly assigned to one of two groups: with the Kinesio tape application from the origin to the insertion of the rectus femoris muscle (14 women) and with the Kinesio tape application from the insertion to the origin of the rectus femoris (16 women). The active and passive knee flexion test was used to evaluate the effectiveness of the Kinesio tape application. The test was performed before applying the tape, immediately after application, three days after wearing the application, and four days after removing the application. Statistical analysis was performed using the Statistica v.13 program and the differences and correlations were considered significant for p < 0.05. Results: The Kinesio tape application increased the range of controlled active knee flexion The research showed a statistically significant increase in the range of active flexion of the knee joint after using both directions of the tape application however, in the E1 group, a difference in the range of motion was observed immediately after application, while in the E2 group after three days of wearing it. In both groups, the effect was maintained on the fourth day after removing the application. Conclusions: The Kinesio tape application may be useful in increasing the range of controlled knee flexion however, it does not improve the range of knee flexion to normal values.